Cascade-Targeting of Charge-Reversal and Disulfide Bonds Shielding for Efficient DOX Delivery of Multistage Sensitive MSNs-COS-SS-CMC - Cui L (Dove Medical Press, 2020)
Lan Cui,1,* Wentao Liu,1,* Hao Liu,1 Qian Qin,1,2 Shuangxia Wu,1 Suqin He,1,3 Zhenya Zhang,4 Xinchang Pang,1 Chengshen Zhu1 1School of Materials Science and Engineering, Zhengzhou University, Zhengzhou 450001, People’s Republic of China; 2Bio & Soft Matter, Institute of Condensed Matter and Nanosciences, Universite Catholique de Louvain, Louvain-la-Neuve B-1348, Belgium; 3Henan Key Laboratory of Advanced Nylon Materials and Application, Zhengzhou University, Zhengzhou 450001, People’s Republic of China; 4Department of Chemistry, Changwon National University of Korea, Changwon-city, Gyeongnam-do 51140, Republic of Korea*These authors contributed equally to this workCorrespondence: Wentao Liu; Hao LiuSchool of Materials Science and Engineering, Zhengzhou University, Zhengzhou 450001, Henan Province, People’s Republic of ChinaEmail wtliu@zzu.edu.cn; hliu@zzu.edu.cnBackground: Although pH and redox sensitiveness have been extensively investigated to improve therapeutic efficiency, the effect of disulfide bonds location and pH-triggered charge-reversal on cascade-targeting still need to be further evaluated in cancer treatment with multi-responsive nanoparticles.Purpose: The aim of this study was to design multi-responsive DOX@MSNs-COS-NN-CMC, DOX@MSNs-COS-SS-CMC and DOX@MSNs-COS-CMC-SS and systematically investigate the effects of disulfide bonds location and charge-reversal on the cancer cell specificity, endocytosis mechanisms and antitumor efficiency.Results: In vitro drug release rate of DOX@MSNs-COS-SS-CMC in tumor environments was 7-fold higher than that under normal physiological conditions after 200 h. Furthermore, the fluorescence intensity of DOX@MSNs-COS-SS-CMC and DOX@MSNs-COS-CMC-SS was 1.9-fold and 1.3-fold higher than free DOX at pH 6.5 and 10 mM GSH. In addition, vesicular transport might be a factor that affects the uptake efficiency of DOX@MSNs-COS-SS-CMC and DOX@MSNs-COS-CMC-SS. The clathrin-mediated endocytosis and endosomal escape of DOX@MSNs-COS-SS-CMC enhanced cellular internalization and preserved highly controllable drug release into the perinuclear of HeLa cells. DOX@MSNs-COS-SS-CMC exhibited a synergistic chemotherapy in preeminent tumor inhibition and less side effects of cardiotoxicity.Conclusion: The cascade-targeting of charge-reversal and disulfide bonds shielding would be a highly personalized strategy for cervical cancer treatment.Keywords: disulfide bonds, pH-triggered charge-reversal, redox sensitive, chitosan oligosaccharide, human cervical carcinoma therapy